Low-frequency noise in oxide-based (TiN/HfOx/Pt) resistive random access memory cells - Fang, Z. (2013)
In this brief, low-frequency noise (LFN) characteristics are studied in oxide-based (TiN/HfOx/Pt) resistive random access nemory cells having different dimensions. It is confirmed that, for the low resistance state (LRS), current conduction is localized without an area dependence, whereas for the high resistance state, it is a uniform leakage current throughout the whole device area. An LFN model is proposed for the filamentary LRS based on the carrier number fluctuation approach, allowing physical analysis of filament characteristics and the surrounding trap concentration.